2012
DOI: 10.1242/jcs.092304
|View full text |Cite
|
Sign up to set email alerts
|

LIMK2 is a crucial regulator and effector of Aurora-A-kinase-mediated malignancy

Abstract: SummaryAurora A is overexpressed in majority of breast carcinomas. With the exception of BRCA1 and PHLDA1, no oncogenic Aurora A substrates are known in breast cancer. In this study, a chemical genetic approach was used to identify malignant targets of Aurora A, which revealed LIMK2 as a novel Aurora A substrate. Aurora A regulates LIMK2 kinase activity, subcellular localization and protein levels by direct phosphorylation at S283, T494 and T505. In response, LIMK2 also positively regulates the level of Aurora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 37 publications
2
62
0
Order By: Relevance
“…Importantly, MLN8237 treatment also reduced AURKA levels as reported previously ( Fig. 2C,F ;Johnson et al, 2012).…”
Section: Aurka Associates With Twist1 and Regulates Its Subcellular Lsupporting
confidence: 88%
See 2 more Smart Citations
“…Importantly, MLN8237 treatment also reduced AURKA levels as reported previously ( Fig. 2C,F ;Johnson et al, 2012).…”
Section: Aurka Associates With Twist1 and Regulates Its Subcellular Lsupporting
confidence: 88%
“…We have previously demonstrated that PHLDA1 decreases AURKA level, whereas LIMK2 increases it (Johnson et al, 2011(Johnson et al, , 2012. Consequently, we investigated whether Twist1 displays a similar effect on AURKA levels.…”
Section: Aurka Inhibits Twist1 Degradationmentioning
confidence: 95%
See 1 more Smart Citation
“…A kinase of interest is engineered (analog-sensitive kinase), which in the presence of a radioactive orthogonal ATP analog (e.g. N6-phenethyl ATP) specifically transfers the radioactive tag to its substrates (Shah et al, 1997;Shah and Shokat, 2002;Shah and Shokat, 2003;Shah and Vincent, 2005;Kim and Shah, 2007;Sun et al, 2008a;Sun et al, 2008b;Chang et al, 2011;Johnson et al, 2011, Johnson et al, 2012. The engineered pocket is generated by replacing a conserved bulky residue (gatekeeper residue) with glycine in the active site of the kinase.…”
Section: Resultsmentioning
confidence: 99%
“…The complementary substituent on ATP is created by attaching bulky groups at the N-6 position of ATP. These ATP analogs are not accepted by wild-type kinases due to steric effects, permitting unbiased identification of direct substrates of the engineered kinase in a global environment (Shah and Vincent, 2005;Kim and Shah, 2007;Johnson et al, 2011;Johnson et al, 2012). Importantly, the sensitized allele created by this mutation has identical substrate specificity to the wild-type kinase.…”
Section: Foxo3a Is a Direct Substrate Of Cdk5mentioning
confidence: 99%